Curd and whey proteins in the nutrition of low birthweight babies. Issue 2 (February 1979) - Berger, H M; Scott, P H; Kenward, C; Scott, P; Wharton, B A
Abstract : Some animals thrive more satisfactorily on a milk that contains whey and curd protein. For this reason human milk protein (which contains about 40% whey) may have some advantages over cows' milk protein (which contains about 15% whey) and so infants feeding formulae based on demineralised whey in which the protein has been modified to achieve a curd:whey ratio similar to that in human milk may also thrive more satisfactorily. As the exact situation in the human newborn is unclear, the effects of feeding a formula containing unmodified cows' milk protein (mainly curd) and one containing the same amount of modified cows' milk protein (curd and whey) were studied in 57 low birthweight babies during the first 3 months of life. During the early weeks of life the curd and whey group grew bigger, absorbed more nitrogen, and excreted proportionately less urea. These results suggest that a curd and whey formula has advantages in the protein nutrition of low birthweight babies, especially the preterm ones. We feel it would be unwise to reduce the protein content of a formula based on cows' milk below 15 g/1 unless it was modified to achieve a larger proportion of whey protein and hence, among other qualities, more cysteine. Although some of the qualities of human milk protein can be mimicked by the use of demineralised whey formulae, others cannot.